INCREASING AWARENESS OF COASTAL AND MARINE ENVIRONMENT FOR TEENAGERS OF HUTUMURI VILLAGE - Tuhumury, Novianty C; Siahainenia, Laura; Louhenapessy, Daniel G; Hulopi, Mahriyana; Sumiyanti, Sumiyanti (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Awareness of the importance of preserving coastal and marine environments can be fostered through various channels. The objective of this community service program (CSP) is to cultivate environmental awareness among adolescents in Negeri Hutumuri, Ambon. The CSP activities were conducted on July 7, 2025, with 52 participants aged 10–15 years. The method used in this CSP is an interactive approach. Materials are presented using images and videos to capture attention and make them easy to remember. The videos shown feature teenagers who are caring and passionate about coastal and marine environments. As a result, participants will be motivated to think critically. Participants were divided into groups to demonstrate their concern and commitment through drawings and sentences on paper, which would later be presented. The participants were highly enthusiastic about participating in this CSP and expressed a desire to become environmental agents within their families and communities.